Maintenance management for construction plant / Mohd Hafiz Abd Khalib - Abd Khalib, Mohd Hafiz (2006)
The usage of plant plays the most important role in construction industry based on its own function. The most important function of plants is to replacing labour where there is a shortage of personnel with necessary skills and reduction in overall construction cost. Thus, the usage of plants should be optimum for the implementations of the project. Lack of maintenance on the construction plant causing low quality of work done, delayed in the completing the project and increasing construction cost. Research carried out, was to measured measure how maintenance of plant that is included in the management of the plant and to identify the weak points in the maintenance management for construction plant. The method was done through direct survey to the company / contractor who involved in construction plant. The findings were that, many problems that occur during do maintenance work / service for construction plant. Thus, it clearly shows that management concerned needs to undertake measures to improve and undertake the existing problem during do maintenance work / service for construction plant.